Two new species of amphibian nematodes from Bhadra Wildlife Sanctuary, Western Ghats, India - Rizvi, Anjum Nasreen (Zootaxa, 2009)
Two new species namely, Cosmocercoides karnatakaensis sp.nov. and Narsingiella clinotarsi sp.nov. from amphibian hosts from Bhadra Wildlife Sanctuary, Western Ghats are described. Cosmocercoides karnatakaensis sp. nov. is characterized by males with small body length, long spicules, small gubernaculum, minute somatic papillae reaching up to esophagus, rosette complex caudal papillae as 8:5:12 pairs and simple caudal papillae as 3:0:0 pairs ; females with small body length, long tail, posteriorly situated vulva and oviparous. Narsingiella clinotarsi sp. nov. is characterized by male having long esophagus, two unequal spicules with trilobed shaft, small gubernaculum and 14 pairs of caudal papillae as 6:1:7 pattern and female having long esophagus, short conical tail and vulva situated at midbody. Both the genera are recorded for the first time from Western Ghats. Key to the species of Cosmocercoides is provided.